Sissieretta Jones : "The Greatest Singer of Her Race," 1868-1933 - Lee, Maureen D. (Book collections on Project MUSE., 2012)
Matilda Sissieretta Joyner Jones, whose nickname the "Black Patti" likened her to the well-known Spanish-born opera star Adelina Patti, was a distinguished African American soprano during the late 19th and early 20th centuries. Performing in such venues as Carnegie Hall and Madison Square Garden, Jones also sang before four U.S. presidents. In this compelling book-length biography of Jones, Maureen Donnelly Lee chronicles the successes and challenges of this musical pioneer. Lee details how Jones was able to overcome substantial obstacles of racial bias to build a 28-year career performing in hundreds of opera houses and theaters throughout North America and Europe. Serving as a role model for other African American women who came after her, Jones became a successful performer despite the many challenges she faced. She confronted head on the social difficulties African American performers endured during the rise of Jim Crow segregation. Throughout her career, Jones was a concert singer performing ballads and operatic pieces, and she eventually went on to star in her own musical comedy company, the Black Patti Troubadours. Critics praised Jones as America's leading African American prima donna, with some even dubbing her voice one in a million. Lee's research, utilizing many black newspapers, such as the New York Age and the Indianapolis Freeman, concert reviews and court documents brings overdue recognition to an important historical songstress. Sissieretta Jones: "The Greatest Singer of Her Race," 1868--1933 provides a comprehensive, moving portrait of Jones and a vivid overview of the exciting world in which she performed.